Clinical Pharmacist-Led Perioperative Management and Pharmaceutical Care in a Patient Undergoing Extended Right Hemicolectomy for Suspected Colon Adenocarcinoma: A Case Report - Mishra, Subhasis; Hegde, Raghavendra Shivaram (Indian Journal of Pharmacy Practice, 2026)
Colorectal cancer is among the most frequently diagnosed malignancies worldwide and a leading contributor to cancer-related mortality. The perioperative course of patients undergoing major colorectal resection is frequently complicated by anaemia, electrolyte disturbances, malnutrition, infection risk, cardiovascular comorbidity and polypharmacy. The clinical pharmacist, as a member of the multidisciplinary surgical team, contributes to medication optimisation, identification and resolution of drug-related problems, antimicrobial stewardship, electrolyte correction, perioperative risk reduction and patient counselling. A 53-year-old woman with a six-year history of hypertension presented with dull, intermittent abdominal pain of four months' duration. Colonoscopy revealed a luminal occluding colonic growth with multiple polyps, and contrast-enhanced computed tomography demonstrated circumferential colonic wall thickening, luminal narrowing and enlarged regional lymph nodes. The carcinoembryonic antigen level was markedly elevated at 83.7 ng/mL. Clinically significant findings included severe anaemia (haemoglobin 7.2 g/dL), hypokalaemia (potassium 2.7 mEq/L), hypoalbuminaemia (albumin 2.3 g/dL) and hypertension. The patient underwent extended right hemicolectomy. The clinical pharmacist conducted structured medication review and provided interventions targeting electrolyte correction, perioperative medication optimisation, antimicrobial stewardship, pain management, cardiovascular monitoring, nutritional support, discharge counselling and medication reconciliation. The patient achieved satisfactory postoperative recovery with stabilisation of clinical and biochemical parameters and was discharged on appropriate medication with structured follow-up advice. This case illustrates the measurable value of clinical pharmacist-led pharmaceutical care in optimising perioperative outcomes in patients undergoing major colorectal cancer surgery and supports the integration of clinical pharmacists within multidisciplinary surgical oncology teams.
Keywords: Antimicrobial Stewardship; Clinical Pharmacist; Colon Adenocarcinoma; Extended; Right Hemicolectomy; Perioperative Care; Pharmaceutical Care